The Effects of 1 mA tACS and tRNS on Children/Adolescents and Adults: Investigating Age and Sensitivity to Sham Stimulation - Maike Splittgerber; Jan Hendrik Suwelack; Navah Ester Kadish; Vera Moliadze (Neural Plasticity)
The aim of this study was to investigate the effect of transcranial random noise (tRNS) and transcranial alternating current (tACS) stimulation on motor cortex excitability in healthy children and adolescents. Additionally, based on our recent results on the individual response to sham in adults, we explored this effect in the pediatric population. We included 15 children and adolescents (10–16 years) and 28 adults (20–30 years). Participants were stimulated four times with 20 Hz and 140 Hz tACS, tRNS, and sham stimulation (1 mA) for 10 minutes over the left M1HAND. Single-pulse MEPs (motor evoked potential), short-interval intracortical inhibition, and facilitation were measured by TMS before and after stimulation (baseline, 0, 30, 60 minutes). We also investigated aspects of tolerability. According to the individual MEPs response immediately after sham stimulation compared to baseline (Wilcoxon signed-rank test), subjects were regarded as responders or nonresponders to sham. We did not find a significant age effect. Regardless of age, 140 Hz tACS led to increased excitability. Incidence and intensity of side effects did not differ between age groups or type of stimulation. Analyses on responders and nonresponders to sham stimulation showed effects of 140 Hz, 20 Hz tACS, and tRNS on single-pulse MEPs only for nonresponders. In this study, children and adolescents responded to 1 mA tRNS and tACS comparably to adults regarding the modulation of motor cortex excitability. This study contributes to the findings that noninvasive brain stimulation is well tolerated in children and adolescents including tACS, which has not been studied before. Finally, our study supports a modulating role of sensitivity to sham stimulation on responsiveness to a broader stimulation and age range.